Natural rubber materials - Thomas, Sabu; Rajisha K. R.; Maria, Hanna J.; Chan, Chin Han; Pothan, Laly A.; Joy, Jithin (RSC polymer chemistry series, 2014)
The combination of its unique morphology, physical properties, cost effectiveness and environmental friendliness make natural rubber an appealing constituent for many materials and applications. This comprehensive two volume set covers the synthesis, characterization and applications of natural rubber based blends, interpenetrating polymer networks, composites and nanocomposites. . Volume 2 focuses on natural rubber-based composites and Nanocomposites including the different types of fillers, the filler-matrix reinforcement mechanisms, manufacturing techniques, and applications